the THE EFFECT OF ZIRCONIUM ADDITIVES ON PROPERTIES OF (Cu22%Zn4%Al) SHAPE MEMORY ALLOY - Zainab Hassan; Ekbal Mohammed Saeed (Mağallaẗ Al-kūfaẗ Al-handasiyyaẗ)
Shape memory alloys (SMAs) are one of the most important types of smart materials. It define as the materials that can undergo large pseudo elastic deformations while having the ability to recover to their original shape once subjected to a memory stimuli such as a specific temperature ,stress ,or strain. This study examines the effects of varying Zirconium (Zr) additive amounts on the microstructure, mechanical, and shape memory effect for all specimens of Cu-Zn-Al SMAs. Powder metallurgy was used to create Cu–22%Zn–4%Al SMAs, both base and with the inclusion of 0.2 and 0.4 weight percent Zr. 650MPa compact pressure was used to create the alloys after the particles had been mixed for five hours. The alloys underwent a three-step sintering procedure in a vacuum tube furnace for one hour at 350 ˚C, then for one hour at 550 ˚C, and for two hours at 850 ˚C. To characterise the microstructural and phase characteristics of alloys, both with and without Zr additions, XRD diffraction analyses, optical microscopy (OM), and scanning electron microscopy (SEM) were performed. With differential scanning calorimetry, the transition temperatures of all alloys were determined (DSC).As well as the shape memory effect test (SME) was measured. Results confirmed that all alloys compositions were found to include the predominant (Cu5Zn8) phase, as proven by XRD and microstructural investigation. The Zr addition dramatically lowered the transition temperatures, according to the transformation temperature data. Hardness experiments reveal that alloys' hardness and volume losses were enhanced by adding up to 0.4% weight percent of Zr reached to (64.8%) and (0.3909)mm3 respectively compared to base alloy.